DESIGN AND IMPLEMENTATION OF RADIO-CONTROLLED CAR LOCK SYSTEM - Abbas, Asif; Kumar, Deepak; Narayan, Vipul (International Journal of Research -GRANTHAALAYAH, 2025)
With the increasing incidents of vehicle theft, tradi- tional security systems have proven inadequate in countering modern-day threats. This paper presents a radio-controlled car locking system that enhances vehicle security using ad- vanced technological measures. The proposed system features radio-controlled locking mechanisms, encrypted communication, backup power solutions, and real-time alerts. These features provide an effective security solution that balances both conve- nience and safety. Additionally, the system is designed to integrate seamlessly with modern vehicle security protocols, providing a comprehensive approach to theft prevention.